2005
DOI: 10.1002/yea.1278
|View full text |Cite
|
Sign up to set email alerts
|

The Gβ(KlSte4p) subunit of the heterotrimeric G protein has a positive and essential role in the induction of mating in the yeast Kluyveromyces lactis

Abstract: In the yeast Saccharomyces cerevisiae the Gβγ dimer of the heterotrimeric G protein transduces a pheromone signal from serpentine receptor to a MAP kinase cascade that activates the mating response pathway. Haploid cells lacking the Gβ subunit do not respond to sexual pheromone, leading to sterility. In this work we demonstrate that the β-subunit of Kluyveromyces lactis, encoded by the KlSTE4 gene, is a component of the G protein, and that its disruption gives rise to sterile cells. However, unlike Ste4p in S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 38 publications
0
37
1
Order By: Relevance
“…We concluded that the absence of Ume6 must affect processes distinct from the a/a repression of hsgs to suppress the mating defect. ume6 is not a bypass suppressor: STE4 encodes the b-subunit of the heterotrimeric G-protein necessary for mating pheromone signaling and is essential for mating in S. cerevisiae (Whiteway et al 1989) and K. lactis (Kawasaki et al 2005). We investigated the possibility that the lack of Ume6 activated an unusual MATa mating pathway that was independent of mating pheromone signaling.…”
Section: Resultsmentioning
confidence: 99%
“…We concluded that the absence of Ume6 must affect processes distinct from the a/a repression of hsgs to suppress the mating defect. ume6 is not a bypass suppressor: STE4 encodes the b-subunit of the heterotrimeric G-protein necessary for mating pheromone signaling and is essential for mating in S. cerevisiae (Whiteway et al 1989) and K. lactis (Kawasaki et al 2005). We investigated the possibility that the lack of Ume6 activated an unusual MATa mating pathway that was independent of mating pheromone signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we conducted further experiments with the KlSte3p receptor. Initially we determined whether KlSte3p is able to physically interact with the G protein involved in transducing the pheromone signal during the mating response of haploid cells (Saviñón-Tejeda et al., , Kawasaki et al, 2005. Previously, we had shown that the cytoplamic C-terminus of the ScSte2p receptor interacts with both the α-and the β-subunits of the heterotrimeric G protein (Duran-Avelar et al, 2001), and that these interactions are required for proper coupling and transmission of the pheromone stimulus (OngayLarios et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment we measured the β-galactosidase activity induced by the magnitude of the interaction between proteins (Figure 4). As a positive control we included the activity induced by the interaction between the Gα (KlGpa1p)-and Gβ (KlSte4p)-subunits, which have shown strong association in previous reports (Kawasaki et al, 2005). Interaction of the KlGpa1p-subunit with the KlSte3p pheromone receptor is three-fold stronger than with the KlGpa2p-subunit, which is involved in regulating cAMP levels upon glucose stimulus in K. lactis (Saviñon-Tejeda et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations